Pelatihan Kepemimpinan Islami bagi Organisasi Siswa SMK Bina Mandiri Multimedia Cileungsi - Muhammad Salman Al Farisi; Ermi Herawati; Humaedi; Viska Yundira (Sekolah Tinggi Ekonomi Bisnis Syariah Bina Mandiri, 2022)
Islamic leadership is an important skill in a leader and depends on him various factors, both internal and external factors based on Islamic values. Currently, the problem of Islamic leadership is an urgent problem, so the phenomenon of a crisis of Islamic leadership arises due to a crisis of trust. One solution that can be put forward is to create individuals who are capable of becoming leaders. This training is a series of activities designed to improve skills, knowledge, experience, or change the attitude of student organization members at SMK Bina Mandiri Multimedia Cileungsi. The method used in carrying out this activity is to conduct training for student organizations in growing the spirit of Islamic leadership in an organization. The purpose of this community service activity is to train students in Islamic leadership management in an organization. The result of this community service activity is that the Intra-School Student Organization or OSIS at SMK Bina Mandiri Multimedia Cileungsi can acquire and learn attitudes, abilities, skills, behavioral knowledge related to Islamic leadership in an organization.